Implementasi Analytic Hierarchy Process (AHP) Dalam Pengambilan Keputusan Desain Kualitas Software - AS SAIDAH, MUTHIAH; Shobri, Muhammad Qolbi; Nasra, Nila Destia (Jurnal Bangkit Indonesia, 2024)
The improvement of software quality is a crucial aspect in software engineering, requiring a profound understanding of the structure and quality available in the market. Software quality involves several external characteristics, such as accuracy, usability, efficiency, reliability, integrity, adaptability, accuracy, and strength, which can be directly observed by users. Therefore, programmers need to ensure that the software they design meets these criteria. In connection with this, this research was conducted to examine the user's perspective on their priorities regarding the eight external characteristic criteria of software using the Analytic Hierarchy Process (AHP) method. This quantitative study aims to determine the priorities chosen by programmers when selecting external characteristics during software design. A sample of 30 individuals who have used selected software was randomly selected for data collection through questionnaires with a Saaty scale of 1-9. Based on the research results, The consistency ratio (CR) of the data is 0.07, indicating that the pairwise comparison criteria provided by the user in the software are consistent because of the value and the eigen vector of the criteria comparison matrix, also known as the user's priority for external software characteristics, was obtained for the eight criteria provided. This priority provides a strong foundation for programmers to focus on aspects considered most important by users.